عوامل تطوير قطاع المؤسسات الصغيرة والمتوسطة في الجزائر - براي, الهادي (جامعة الوادي - University of Eloued, 2020)
تناولت هذه الدراسة إشكالية المؤسسات الصغيرة والمتوسطة وعوامل تنميتها لحالة الجزائر، وكان هدفنا تشخيص حالة المؤسسات الصغيرة والمتوسطة في الجزائر، والتعرض لتأهيل المؤسسات الصغيرة والمتوسطة ، وهيئات دعم المؤسسات الصغيرة والمتوسطة في الجزائر واستخدمنا المنهج الوصفي التحليلي، من خلال عدة عناصر أساسية، واستنتجنا أن الجزائر اعتمدت على سياسة تشجيع وتدعيم إنشاء المؤسسات الصغيرة والمتوسطة من أجل تفعيل دورها في الاقتصاد، وكما لاحظنا أن الجزائر بحاجة إلى زيادة العمل من أجل توجيه قطاع المؤسسات الصغيرة والمتوسطة نحو القطاعات الاقتصادية الأساسية كالصناعة والزراعة. This study dealt with the problem of small and medium enterprises and their development factors for the case of Algeria, and our goal was to diagnose the situation of small and medium enterprises in Algeria, and exposure to the rehabilitation of small and medium enterprises, and organizations supporting small and medium enterprises in Algeria, and we used the descriptive and analytical approach, through several basic elements, and we concluded that Algeria adopted On the policy of encouraging and supporting the establishment of small and medium enterprises in order to activate their role in the economy, and as we have noted that Algeria needs to increase work in order to direct the small and medium enterprises sector towards basic economic sectors such as industry and agriculture
Factors for developing the small and medium enterprises sector in Algeria
مقال
Keywords: مؤسسات صغيرة ومتوسطة، تأهيل، دعم....